2013
DOI: 10.1371/journal.pone.0053767
|View full text |Cite
|
Sign up to set email alerts
|

t(8;9)(p22;p24)/PCM1-JAK2 Activates SOCS2 and SOCS3 via STAT5

Abstract: Fusions of the tyrosine kinase domain of JAK2 with multiple partners occur in leukemia/lymphoma where they reportedly promote JAK2-oligomerization and autonomous signalling, Affected entities are promising candidates for therapy with JAK2 signalling inhibitors. While JAK2-translocations occur in myeloid, B-cell and T-cell lymphoid neoplasms, our findings suggest their incidence among the last group is low. Here we describe the genomic, transcriptional and signalling characteristics of PCM1-JAK2 formed by t(8;9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 52 publications
4
24
0
Order By: Relevance
“…Cell cycle checkpoints, which can be activated as a result of DNA damage or exogenous stress signals are cell-intrinsic mechanisms that prevent cells from developing a malignant phenotype. 37 Previous cytogenetic studies revealed an accumulation of chromosome aberrations during the progression from LyP to PCALCL and MF, 25,38,39 indicating an impaired cell-cycle checkpoint during the malignant progression. Our study suggests that the cytogenetic abnormalities during disease progression may be attributed to SATB1 aberrancy-induced G1/S checkpoint disruption in CD30 1 lymphoma cells.…”
Section: Satb1 Upregulation During Disease Progression Is Associated mentioning
confidence: 99%
See 1 more Smart Citation
“…Cell cycle checkpoints, which can be activated as a result of DNA damage or exogenous stress signals are cell-intrinsic mechanisms that prevent cells from developing a malignant phenotype. 37 Previous cytogenetic studies revealed an accumulation of chromosome aberrations during the progression from LyP to PCALCL and MF, 25,38,39 indicating an impaired cell-cycle checkpoint during the malignant progression. Our study suggests that the cytogenetic abnormalities during disease progression may be attributed to SATB1 aberrancy-induced G1/S checkpoint disruption in CD30 1 lymphoma cells.…”
Section: Satb1 Upregulation During Disease Progression Is Associated mentioning
confidence: 99%
“…2 To further quantify SATB1 expression during disease progression, we first studied cells established from a patient who progressed from LyP to PCALCL. 5,25 In this case, the Mac-1 cell line was derived during an indolent course of disease, whereas the Mac-2A and Mac-2B cells were derived from separate rapidly growing skin tumors 3 years later in disease progression. These cells are representative of the primary tumors and retain the features of the original lymphoma.…”
Section: Statisticsmentioning
confidence: 99%
“…This is where cytogenetics can come to the rescue, at least where karyotypic data have been published, since most cell line karyotypes are effectively unique. That of the anaplastic large cell lymphoma cell line MAC-2A (Figure 2.4.1a, lower panel), although closely related to those of its sister cell lines MAC-1 and MAC-2B, is still readily distinguishable from its siblings [24].…”
Section: Authentication and Cross-contaminationmentioning
confidence: 99%
“…Moreover, GEP data may provide further prognostic stratification of PTCLs [45,47]. Finally, although comprehensive profiling of recurrent somatic mutations in ALCL requires further effort, recent data indicate recurrent abnormalities targeting the JAK-STAT pathway, particularly point mutations of JAK1 and STAT3 but also including novel fusion genes [4850]. These findings suggest a potential target for novel therapeutic approaches in at least some ALCLs.…”
Section: Pathobiologymentioning
confidence: 99%